Status of Marine Birds of the Southeastern Beaufort Sea - Dickson, D. Lynne; Gilchrist, H. Grant (ARCTIC, 2002)
This summary and update of information on the marine birds of the southeastern Beaufort Sea is intended to support discussions on how to improve management of marine resources in the Canadian Beaufort Sea region. Perhaps the most outstanding use of the Beaufort Sea by marine birds is the staging during spring migration by hundreds of thousands of eiders and long-tailed ducks in the early open water off Cape Bathurst and Banks Island. During midsummer, tens of thousands of long-tailed ducks, scoters, scaup, and mergansers moult in the sheltered bays and behind barrier beaches and spits. Although several species of geese, ducks, loons, gulls, and terns nest on islands and in wetlands along the Beaufort Sea coast, this region has relatively few nesting seabirds compared to eastern Arctic Canada and the Bering Sea. Two possible reasons for this are a shortage of cliffs suitable for nesting and a lack of pelagic fish. The five most common sea duck species that occur in the region, long-tailed duck, king eider, common eider, surf scoter, and white-winged scoter, have all declined in numbers since the mid-1970s. Western Arctic brant populations have also declined, although their status within the Beaufort Sea region is unclear. Brant and king eider are the only marine bird species harvested there in substantial numbers. Other threats to Beaufort Sea marine bird populations include oil spills, global warming, coastal development, and contaminants. Certain threats can be managed at a local level since they are a result of local economic development, but others, such as global warming or loss of critical wintering areas, stem from environmental problems outside the region. Solving these issues will require mutual understanding and commitment on the part of numerous countries. Cette récapitulation et mise à jour de l'information sur les oiseaux marins du sud-est de la mer de Beaufort ont été faites dans le but de fournir des arguments sur la façon d'améliorer la gestion des ressources marines dans la zone canadienne de ...